Midline Household Survey Results: Karnal, Haryana State, India - Jagannath, Pratyaya; Raj; Nagpal, Mansi; Khatri-Chhetri, Arun (2019)
In 2011, CCAFS carried out baseline surveys (household survey, a village study and an organizational survey) in 21 research sites across 17 countries within its five focus regions, using standardized baseline tools in each site. Many years after the implementation of the baseline studies, CCAFS has conducted the midterm evaluation surveys, which are compared with the baseline findings to track the performance of Climate-Smart Village (CSV) sites and measure the impact on beneficiaries. With a few improvements, the same standardized tools were used again to carry out the midline evaluation and to ensure comparability with the data collected previously.